Grammatical Cohesion in Some Selected Political Texts - Salim Hmood, Saddam (Journal of College of Education, 2020)
This research intends to investigate one of the features of the text, it is about a grammatical cohesion. It will show an idea about cohesion and how it is used in the political texts, Moreover, how the politicians make use of cohesion in their political speeches. An analysis will be applied on a political text , the analysis attempts to explain the importance of a grammatical cohesion and its role in enhancing the cohesion of the text . However, the study aims at carrying an analysis of cohesion in selected political texts to find out how it integrates the texts under investigation, . It is hypothesized that cohesion is available in the political texts through the use of the cohesive devices. The whole results reveal that that politicians use the majority of grammatical cohesive devices in their political speeches. The findings also showed that the reference especially the general reference is the most apparent in the political text understudy because politicians are very cautious in their speech. The second one is the conjunction. The last one is the abbreviation .